THE RELATIONSHIP BETWEEN MEDICATION TIMELINESS AND FLUID CONSUMPTION ON RECURRENCE OF HEART FAILURE PATIENTS: HUBUNGAN KETEPATAN WAKTU MINUM OBAT DAN KONSUMSI CAIRAN TERHADAP KEKAMBUHAN PASIEN GAGAL JANTUNG - Ramadhan, Azhar; Nuraeni, Ani; Manurung, Suryani (Essential English Grammar, 2025)
Heart failure is a condition when the heart is unable to pump blood optimally, resulting in the distribution of oxygen and nutrients throughout the body. Recurrence often occurs in patients with a history of heart failure, especially due to non-compliance in taking medication and uncontrolled fluid intake. This study aims to analyze the relationship between the timeliness of taking medication and fluid consumption on recurrence in patients with heart failure. The design used was quantitative with a retrospective cross-sectional approach, involving 93 respondents who underwent re-hospitalization at one of the hospitals in Depok City, West Java. The sampling technique used consecutive sampling. Data were collected through three variables that had been tested for validity and reliability, including demographic characteristics, recurrence history, medication compliance, and fluid consumption. Data were analyzed using the Gamma and Somers'd correlation tests with the help of SPSS. The results showed a significant association between medication adherence and relapse (p < 0.05), while fluid consumption did not show a significant association (p > 0.05). These findings suggest the importance of medication adherence education as part of nursing interventions to prevent recurrence in heart failure patients. Fluid consumption requires further study in future research.